Preparation of Problem Solving Skills Assessment for Senior High School Students on Environment Material - Naintyn Novitasari; Murni Ramli; Maridi Maridi (Universitas Sebelas Maret, 2015)
Has been done research that aims to figure out the character of assessment problem solving skillsof high school student. the assessment problem solving was designed such that the results would describe the degree to which students are able to confront, structure, represent and solve the problems effectively. Data were taken through test technique and qualitative analysis done by the assessment expert. Quantitative datawere takenfromstudents' responseson the testsof problem solving while qualitative datawere taken from the resultsof qualitative analysis. The data were analyzedqualitativelyincludes ofthe construction, materialandlanguage. Quantitative data analysis used percentage formula which includes the difficulty index and the discriminating index. According to the result and discussion of the data analysis, it can be included that the arranged assessment was problem solving skills on senior high school students especially in the environment material. The Assessment constructed by 18 problem solving skills indicators thatconsistsoftwocases. Each of casas consits of 18 item and the students were given 60 minutes to do the best. The final result of the first case are 77,7% item were accepted, 16,7% item were revised and 5,6% item were rejected. While for second case 100% item were accepted, 0% item were revised and 0% item were rejected.Keywords: assessment, problem solving skills